SISTEM INFORMASI PENGELOLAAN DAN ANALISA PERSEDIAAN BARANG METODE RASIO BERBASIS WEB - Sri Wahyuning Wahyuning; Anif Maghfiroh; Haryo Kusumo; Eko Siswanto (Universitas Sains dan Teknologi Komputer, 2023)
Financial management is an administrative activity related to budget planning, storing, using, recording and monitoring the entry and exit of money or organizational funds. Inventory analysis is an activity to examine an asset issue that includes goods. Turn over inventory is the ratio between the total cost of goods sold and the average value of inventory owned by the company. in the process of managing finances and inventories, it is still carried out using a recording system in a ledger, so it is less effective. Therefore the author will develop a form of information system by selecting CV. Arris AC as research object. Based on the problems that occur in CV. Arris AC, the authors provide a solution that can overcome weaknesses by creating an Accounting Information System for Financial Management and Inventory Analysis using the inventory turnover ratio method which can be accessed via the web. In other words, this ratio describes how fast inventory rotates. web is an application that contains multimedia documents (text, images, sound, animation, video) in it that uses the HTTP protocol with database support for MySQL, Xampp and Adobe Dreamweaver CS6.. Keywords:Accounting, Financial Management, Inventory Analysis, Ratio, Web